This preview shows page 1. Sign up to view the full content.
Unformatted text preview: = 2 y + x 3 cos( x ) (d) y = 2 xy + 3 x 2 e x 2 (e) ( x 2 + 4) y + 3 xy = x (f) ( x 2 + 1) y + 3 x 3 y = 6 xe-3 2 x 2 (2) Application: The equation y = ky models wide range of natural phenomenaany involving a quantity whose time rate of change is proportional to its current size. Continuously Compounded Interest Rate: Let P ( t ) denote principle at time t, which will earn interest with rate r ( t ) and compounded continuously, we have dP dt = rP. Now...
View Full Document
- Spring '11